Family murder in post-apartheid South Africa: reflections for mental health professionals - M C Marchetti-Mercer (AOSIS, 2003)
In the late eighties the phenomenon of family murder was closely linked to Afrikaans-speaking families faced withpolitical change and uncertainty. Opsomming In die laat 1980s het die opvatting ontstaan dat daar 'n noue verband bestaan tussen gesinsmoord en Afrikaansprekende gesinne wat met politieke veranderinge en onsekerheid gekonfronteer word. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.